Evaluation of Antibacterial Properties of some Medicinal Plants used for the Treatment of Respiratory Tract Infections in Nepal - Kunwor, Rup Bahadur; Thapa, Olivia (Tribhuvan University Journal, 2013)
The present work was designed to evaluate the antibacterial properties of the ethanol extracts of five selected medicinal plants Azadirachta indica, Ocimum sanctum, Jasminium humile, Glycyrrhiza glabra and Acorus calamus on bacteria causing respiratory tract infections. Almost all the tested medicinal plants showed inhibitory effect against the test organisms. Among the medicinal plants evaluated Ocimum sanctum was found effective against most of the testorganisms except Pseudomonas aeruginosa. The growth of Staphylococcus aureus was inhibited by all tested plant extracts with highest zone of inhibition by G. glabra with ZOI value 23 mm and MBC value 0.39 mg/ml in ethanol suspension. Among the test organisms K. pneumoniae was found more resistant towards the test plant extracts. This bacterium was inhibited only by J. humile with ZOI value 13 mm and MBC value 6.25 mg/ml in alcohol solution. The present work evidently provides information on the role of some medicinal plants in the fight against bacteria causing respiratory tract infections.